EVALUATION OF BROWNFIELDS IN LATVIA (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Brownfields (contaminated or degraded territories) significantly pollutes environment, form derelict landscapes and affects people’s security and health. Formation of these sites depends on many factors such as bad industrial practise and economy, inadequate legislation, wastewater and waste management etc. Inventory and evaluation of these sites in Latvia is carried out according to Regulations issued by the Latvia Cabinet of Ministers. The sites are characterised with parameters which differs from accepted in the other European countries. For example, primary classification indicator in Latvia is a degree of ground and soil pollution in these fields and as a secondary factor – presence of destroyed and abandoned buildings. The paper presents the results of investigation the situation on brownfields in Latvia, especially in Rezekne city, analyses the reasons of their formation and develops recommendations for intensification revitalization process of brownfields.